Cloud analytics with microsoft azure : build modern data warehouses with the combined power of analytics and azure - Altaiar, Has (PACKT Publishing, 2019)
Cloud Analytics with Microsoft Azure is an end-to-end guide to processing and analyzing big data using a range of Microsoft Azure features. This book covers everything you need to build your own data warehouse and learn numerous techniques to gain useful insights by analyzing big data.